The Increase in Balloon Size to Over 15 mm Does Not Affect the Development of Pancreatitis After Endoscopic Papillary Large Balloon Dilatation for Bile Duct Stone Removal - Youn, Young Hoon (Springer US, 2010)
BACKGROUND: Endoscopic papillary large balloon dilatation (EPLBD) after endoscopic sphincterotomy (EST) has recently become widely used for common bile duct (CBD) stone removal, but many clinicians remain concerned about post-procedural pancreatitis with increasing the balloon size to over 15 mm. AIMS: We aimed to evaluate the safety and efficacy of EPLBD with a relatively large balloon (15–20 mm) after EST and to evaluate the factors related to post-EPLBD pancreatitis. METHODS: A retrospective review was undertaken of the endoscopic database of 101 patients with CBD stones who underwent EPLBD using a larger balloon size of over 15 mm (15–20 mm). Clinical parameters, endoscopic data, and outcomes were analyzed. RESULTS: The mean age of the subjects was 69 years. All patients had a dilated CBD of over 11 mm (mean = 22.6 mm). The mean size of balloon used in EPLBD was 17.1 ± 1.9 mm (range 15–20 mm). Mechanical lithotripsy was required in seven patients (6.9%). The rate of complete stone removal in the first session was 92.1%. Post-procedural pancreatitis developed in five cases (5.4%), but none were graded as severe. The smaller dilatation of the CBD, longer cannulation time, and longer time for stone removal were associated with post-procedural pancreatitis, but larger size of balloon did not affect the development of post-EPLBD pancreatitis. CONCLUSIONS: EPLBD with a large balloon of over 15 mm with EST is an effective and safe procedure with a very low probability of severe post-procedural pancreatitis. Post-EPLBD pancreatitis was not associated with larger balloon size, but was associated with longer procedure time and smaller dilatation of the CBD.